(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Mental health disorders such as stress, anxiety, and depression are increasing rapidly across all age groups. Many individuals do not receive timely support due to limited access to professional mental healthcare services. Artificial intelligence–based voice assistants provide a new opportunity to offer emotional support and continuous mental health monitoring. This paper surveys voice-based artificial intelligence mental health companions integrated with emotion tracking systems. The study reviews existing technologies, emotion detection techniques, system architectures, and practical applications. It also discusses major challenges including privacy, ethical responsibility, and emotional accuracy. The survey highlights that combining voice interaction with emotion tracking can significantly improve accessibility and user engagement in mental healthcare systems. This paper aims to provide a comprehensive overview for researchers and developers working in the field of intelligent mental health support systems.